Diplomasi Panda dan Hubungan Bilateral China-Jerman Tahun 2016-2019 - Sasmita, Anggraini Ika; Utomo, Ario Bimo (Department of International Relations, Brawijaya University, 2021)
Since the 7th century, China has been giving their endemic animal, Giant Panda, as one of public diplomacy practice also known as Panda Diplomacy. China’s Panda Diplomacy only applies to countries that have profitable historical trade with China. This Research will discuss on how China’s government effort to implement panda diplomacy to Germany, which has been the high-technology main importer country for China since 1999. However the relations ever been on a tense stage, since Germany considered China as a competitor. To keep rhe good relation market with Germany, Xi Jinping commanded China’s Wildlife Conservation and Association to lend a giant panda as a friendship symbol for both countries. This paper employs a qualitative method using Eytan Gilboa framework to analyze public diplomacy application with timw, purpose, public opinion, government and instrument as the research variable. From those variables will shown how panda diplomacy as a public diplomacy practice with long term relations as a result. Keywords : Public Diplomacy, Panda Diplomacy, China, Germany